ANALISIS PENGARUH EKONOMI TERHADAP KEPERCAYAAN DIRI SISWA - Adela Yasica (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
Abstract : There are many factors that affect the nature of students, especially students who are in Indonesia. Starting from environmental factors to family economic factors that are able to be the background for the extent to which the student develops. The development of students who are basically teenagers who are looking for their identity is very easily influenced by many aspects of life. This is true in affecting the extent to which students will develop. Student development is also one of the main factors in determining the future of shiva and student life in the school and community environmentKeywords : student, economy, schoolAbstrak : Banyak factor yang mempengaruhi sigat sifat siswa khususnya siswa yang berada di Indonesia. Mulai dari factor lingkungan hingga factor ekonomi keluarga yang mampu menjadi latar belakang sejauh mana siswa itu berkembang. Perkembangan siswa yang pada dasarnya merupakan remaja yang tengah mencari jati diri mereka sangatlah mudah dipengaruhi oleh banyak aspek kehidupan. Hal ini benar benar mepengaruhi sejauh mana siswa akan berkembang. Perkembangan siswa juga menjadi salah satu factor utama dalam menentukan masa depan siwa dan kehidupan siswa di lingkungan sekolah maupun bermasyarakatKata Kunci : siswa, ekonomi, sekolah